Epistemological Basis of Guidance and Counseling Science in the Era of Rapid Social and Cultural Change - Yona Apriliana; Yeni Karneli; Puji Gusri Handayani (Aimmah: Social Sciences Journal, 2025)
The rapid pace of social and cultural change necessitates a re-evaluation of the epistemological foundations of Guidance and Counseling, particularly within multicultural societies. This article aims to critically examine the epistemology of counselling by emphasizing the importance of contextual and reflective approaches grounded in local values. Employing a qualitative method through a literature review, data were collected using documentation techniques and analyzed through content analysis of relevant academic sources. The findings reveal that the dominance of Western paradigms in counselling epistemology needs to be complemented with indigenous approaches that are more adaptive to socio cultural dynamics. This study contributes theoretically to the development of counselling as a humanistic and culturally sensitive discipline, while also encouraging curriculum reform and inclusive counseling practices. Future research is recommended to empirically validate these conceptual findings through field studies and real world counseling practice.